Female oldness: social memory and grandmothering (PerCursos, 2023)
The process of female aging and the experience of grandmotherhood is a central element in the discussion of patriarchal society and its manifestations. Therefore, this article aims to reflect on female old age and its relationship with grandparenthood, synthesizing discussions based on the construction of the thesis “the visibility of elderly women in contemporary times: building perspectives on new concepts of grandparenthood”. It also intends to emphasize the importance of female aging in a critical perspective, thus enabling reflection on the historical oppressions experienced in patriarchal societies. And so encouraging responses through the intersectional approach intertwined with the discussion of grandparents, memory and social identity. This article aims to contribute theoretically to related studies in a multidimensional perspective of old age in contemporary times.
Keywords: oldness; female; grandmothering; social memory